2016
DOI: 10.1039/c5dt03598h
|View full text |Cite
|
Sign up to set email alerts
|

p-Tolylimido rhenium(v) complexes with phenolate-based ligands: synthesis, X-ray studies and catalytic activity in oxidation with tert-butylhydroperoxide

Abstract: The reactions of mer-[Re(p-NTol)X3(PPh3)2] (X = Cl, Br) with chelating phenolate-based ligands (2-(2-hydroxy-5-methylphenyl)benzotriazole (HL(1)), 2-(2-hydroxyphenyl)benzothiazole (HL(2)) or 2-(2-hydroxyphenyl)benzoxazole (HL(3))) afforded a series of p-tolylimido rhenium(v) complexes cis- or trans-(X,X)-[Re(p-NTol)X2(L)(PPh3)]·yMeCN (where X = Cl, Br; L = L(1), L(2), L(3) and y = 0-2) and [Re(p-NTol)X(L)(PPh3)2]Z·pPPh3 (where X = Cl, Br; Z = ReO4, PF6; L = L(1), L(2), L(3) and p = 0 or 1). The reported compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 141 publications
1
6
0
Order By: Relevance
“…It can be seen that hydrogen atoms in position 4 posess lower activity, aparently due to some sterical hindrance [50,57,60]. The bond-selectivity parameter (1 • :2 • :3 • ; the relative normalized reactivities of hydrogen atoms at the primary, secondary, and tertiary carbons) in the oxidation of methylcyclohexane (1.0:6.7:17.5) is close to the corresponding values found for the systems oxidizing alkanes with hydroxyl radicals (see, for example, References [69][70][71][72][73][74][75]). The oxidation of cis-1,2-dimethylcyclohexane proceeds non-stereoselectively, because the trans/cis ratio [the ratio of isomers of tert-alcohols with mutual transand cis-orientation of two methyl groups] of isomeric alcohols (after reduction with PPh 3 ) was 0.8.…”
Section: Selectivity In the Alkane Oxidationssupporting
confidence: 65%
“…It can be seen that hydrogen atoms in position 4 posess lower activity, aparently due to some sterical hindrance [50,57,60]. The bond-selectivity parameter (1 • :2 • :3 • ; the relative normalized reactivities of hydrogen atoms at the primary, secondary, and tertiary carbons) in the oxidation of methylcyclohexane (1.0:6.7:17.5) is close to the corresponding values found for the systems oxidizing alkanes with hydroxyl radicals (see, for example, References [69][70][71][72][73][74][75]). The oxidation of cis-1,2-dimethylcyclohexane proceeds non-stereoselectively, because the trans/cis ratio [the ratio of isomers of tert-alcohols with mutual transand cis-orientation of two methyl groups] of isomeric alcohols (after reduction with PPh 3 ) was 0.8.…”
Section: Selectivity In the Alkane Oxidationssupporting
confidence: 65%
“…During the past several decades, many metals have been studied in catalytic activation and functionalization of carbon-hydrogen bonds. The reader is directed to selected recent examples with gold [123], cobalt [124][125][126] chromium [127], copper [128][129][130][131] iron [132][133][134][135], iridium [136], manganese [137][138][139], molybdenum [140], nickel [141], osmium [142][143][144][145][146][147][148], palladium [149][150][151], rhenium [152], rhodium [153,154], ruthenium [155,156], and vanadium [157,158].…”
Section: Metal Ions Most Active In Oxidation Catalysismentioning
confidence: 99%
“…Machura et al [79] described the oxidation of inert alkanes to alkyl hydroperoxides by H2O2 catalyzed with monomeric oxovanadium(V) complexes of 8-hydroxyquinoline derivatives as noninnocent ligands (Scheme 4). The analogous ligands in complexes with copper or rhenium were used in oxidations by peroxides [80][81][82][83] Gushchin, Kuznetsov, et al recently [84,85] observed high activity among the vanadium complexes shown in Scheme 5 in the oxidation of hydrocarbons with peroxides. The mechanism for the generation of OH radicals is presented in Scheme 6.…”
Section: Oxidation Of Hydrocarbons and Alcohols With Peroxides Catalymentioning
confidence: 99%
“…Machura et al [79] described the oxidation of inert alkanes to alkyl hydroperoxides by H2O2 catalyzed with monomeric oxovanadium(V) complexes of 8-hydroxyquinoline derivatives as noninnocent ligands (Scheme 4). The analogous ligands in complexes with copper or rhenium were used in oxidations by peroxides [80][81][82][83] Scheme 4. Cleavage of the HO-OH bond and intramolecular electron transfer in a vanadium complex in the absence of PCA.…”
Section: Oxidation Of Hydrocarbons and Alcohols With Peroxides Catalymentioning
confidence: 99%